Trade Unions in the Transition to Democracy: A Comparative Analysis of the Impact in Chile and Spain (Comillas Journal of International Relations, 2021)
The relevance of trade unions as social movements in the study of the transition to democracy has not been taken into account as much as the leadership of parties and politicians. Through the theory that studies the conditions in which social movements have more capacity for political and social impact, we analyze what were the characteristics of the transitions in Chile and Spain and of the unions that had more impact during them. These characteristics include the structure of political opportunity, the discursive and identity framework of the unions, and their repertoires of action. Through this analysis, it can be seen that the structure of opportunity largely conditions the unions' capacity for action.
Keywords: trade unions; social movements; transition; structure of political opportunity; Pedro Ibarra; Sydney Tarrow